China's grand strategy : a roadmap to global power? - Denoon, David (New York University Press, 2021)
"China's dramatic rise on the world stage was evident by the last decade of the 20th Century. In the period 1979 - 2008, China played a low-keyed role, emphasizing economic growth and cooperative relations with other countries. However, since the global recession of 2008-2009, China has been more aggressive in both its economic and foreign policy. The goal of this volume is to assess China's intentions and to evaluate what the Chinese leadership hopes to achieve by such actions as occupying the atolls in the S. China Sea and implementing its massive aid program, The Belt and Road Initiative. The volume includes authors with varying perspectives on China's intentions so the reader can compare competing viewpoints on China's plans"--